An Islamic Legal Analysis of the Ngemblok Tradition in Mentoro Village: A Study from the Perspective of Fathul Qorib - Farichatul Aula Nikmatur Rohmah; Masrokhin (Justicia Religia, 2026)
The Ngemblok Tradition in Mentoro Village, Tuban Regency, is a marriage proposal practice initiated by the female party toward the male party, which differs from the conventional practice of khitbah commonly found in Muslim communities. This study aims to analyze the implementation of the Ngemblok tradition and examine its relevance to the concept of khitbah in the Book of Fathul Qorib and the perspective of Islamic law. This research employs a qualitative method with a socio-juridical approach through a field case study. Data were collected through observation, in-depth interviews with four informants selected using purposive sampling techniques, and documentation. The research informants consisted of the Head of Mentoro Village, religious figures, and practitioners of the Ngemblok tradition. The findings reveal that the Ngemblok tradition is carried out through family deliberation and involves community leaders to preserve the values of propriety, harmony, and mutual respect between families. The analysis of the Book of Fathul Qorib indicates that although khitbah is described as a proposal initiated by the male party toward the female party, there is no explicit provision prohibiting women from proposing marriage to men. Based on the principle of al-'adah al-muhakkamah, the Ngemblok tradition can be categorized as 'urf shahih because it has become an accepted custom within the community, does not contradict the principles of Islamic law, and provides benefits in the process of establishing a family. The novelty of this study lies in its analysis of the Ngemblok tradition by directly connecting it with the concept of khitbah in the Book of Fathul Qorib and the principle of al-'adah al-muhakkamah as a basis for legitimizing customary practices within Islamic law.